Fostering or Hindering? A Systematic Review on the Influence of Artificial Intelligence in Education - Jin, Haibo; Bilfqih, Ghizlane (International Journal of Language and Literary Studies, 2026)
This review paper aims to examine the influence of Artificial Intelligence in Education (AIED) on the development of 21st century skills. A systematic literature search was conducted using academic databases including Science Direct, Scopus, and Google Scholar, employing keyword combinations such as “Artificial Intelligence”, “AI”, “6C skills”, which cover the publications primarily from 2012 to 2024. Thematic analysis was performed following the Maximum Data Quality Assurance framework to ensure rigorous categorization and interpretation of the selected studies. The findings indicate that AIED significantly affects the 6C skills—namely character, citizenship, critical thinking, creativity, collaboration, and communication. AI technologies are increasingly employed to address diverse educational challenges and enhance learning processes. However, the relationship between AI and skill development is bidirectional: while AI facilitates personalized learning and supports students with learning difficulties, it also presents certain risks. Specifically, overreliance on AI tools may lead to a decline in learners’ critical thinking, creativity, and moral reasoning abilities. This review highlights the dual-edged nature of AIED, underscoring the need for balanced integration that maximizes benefits while mitigating potential drawbacks to 21st century skill development.